2016
DOI: 10.1590/1517-869220162203137068
|View full text |Cite
|
Sign up to set email alerts
|

Respostas De Indicadores Fisiológicos a Um Jogo De Futebol

Abstract: RESUMO Introdução: A performance no futebol depende de vários fatores, entre eles, conhecimento das alterações fisiológicas ocorridas durante o jogo. Objetivo: Identificar as alterações hematológicas, imunológicas, enzimáticas, hormonais e inflamatórias decorrentes do aumento de suas concentrações plasmáticas após um jogo de futebol. Métodos: A amostra foi constituída por 42 atletas do sexo masculino, com média de idade de 25,7 ± 4,6 anos, todos profissionais da modalidade futebol. Todos os atletas particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
2
5
0
6
Order By: Relevance
“…The latter author, however, did not report the interval between CK collection and team training. In relation to LDH, Bezerra et al (2016) found resting values close to those of the present study and reported that the interval between the final training and collections was 24 h, suggesting that the values found were influenced by the daily training. Ispirlidis et al (2008) , when evaluating professional soccer players, pre- and post-game, found CK and LDH resting values below 200 U/L, however the author states that the athletes did not practice any strenuous activity for 7 days before and after the game.…”
Section: Discussionsupporting
confidence: 88%
“…The latter author, however, did not report the interval between CK collection and team training. In relation to LDH, Bezerra et al (2016) found resting values close to those of the present study and reported that the interval between the final training and collections was 24 h, suggesting that the values found were influenced by the daily training. Ispirlidis et al (2008) , when evaluating professional soccer players, pre- and post-game, found CK and LDH resting values below 200 U/L, however the author states that the athletes did not practice any strenuous activity for 7 days before and after the game.…”
Section: Discussionsupporting
confidence: 88%
“…Estas ações motoras provocam um alto desgaste psicofisiológico ao jogador, caracterizando assim as demandas do atleta de futebol como intermitente de alta intensidade [1,13,14]. As demandas metabólicas do atleta devem ser avaliadas e interpretadas de forma a propiciar informações reais sobre condições dos jogadores e possíveis elaborações de estratégias de treino, bem como de aprimoramento de capacidades físicas que poderão determinar o desempenho do jogador [15].…”
Section: Introductionunclassified
“…Regarding its characterization, soccer has been considered an intermittent modality as its official matches require numerous motor actions, such as accelerations/decelerations, jumps and changes of direction at different intensities, and the competitive performance of players can be influenced by the interaction of different motor skills 1,2 .…”
Section: Introductionmentioning
confidence: 99%